Differential carbon utilization and asexual reproduction under elevated pCO2 conditions in the model anemone, Exaiptasia pallida, hosting different symbionts. (9th September 2015) - Hoadley, Kenneth D.; Rollison, Dana; Pettay, D. Tye; Warner, Mark E.
Abstract: Here we report the effects of elevated p CO2 on the model symbiotic anemone Exaiptasia pallida and how its association with three different strains of the endosymbiotic dinoflagellate Symbiodinium minutum (ITS2‐type B1) affects its response. Exposure to elevated p CO2 (70.9 Pa) for 28 d led to an increased effective quantum yield of PSII in actinic light within two of the alga‐anemone combinations. Autotrophic carbon fixation, along with the rate of carbon translocated to the animal, were significantly elevated with high p CO2 . Elevated p CO2 exposure also coincided with significantly greater asexual budding rates in all tested anemones. Further, differences in photochemistry and carbon translocation rates suggest subtle differences in the response to p CO2 among the three strains of S. minutum and their host anemones. This illustrates the potential for physiological diversity at the subspecies level for this ecologically important dinoflagellate. Positive alterations in photosynthesis, carbon utilization, and fitness within this model symbiosis suggest a potential benefit from ocean acidification (OA) not yet observed within corals, which may enable these anthozoans to gain a greater ecological presence under future OA conditions.